Standardization of the Ethanol Extract of Mahkota Dewa Leaves (Phaleria macrocarpa (Scheff.) Boerl) Using Non-Specific Parameters - Wa Ode Sitti Musnina; Dwi Ayu Reskia Anwar; Agustinus Widodo; Akhmad Khumaidi (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: Medicinal plant extracts have been widely developed for use in health services. Medicinal plant extracts derived from raw material can be used in the form of dry, viscous, and liquid extracts according to the active ingredients contained therein and the intended use. Traditional medicines circulating in Indonesia must meet quality, safety, and efficacy. One of the medicinal plants whose empirical use is widely known by the people of Indonesia is Mahkota dewa (Phaleria macrocarpa (Scheff.) Boerl). Purpose: It is to standardize the ethanol extract of Mahkota Dewa leaves to ensure its quality, safety, and pharmacological properties. The standardization carried out is non-specific parameters based on Indonesian Herbal Pharmacopeia. Methods: The leaves of Mahkota Dewa were collected from Parigi Moutong, Donggala, and Sigi Regon, and extracted using maceration method with ethanol. The ethanol extract was then tested for non-specific parameters including drying shrinkage, water content, total ash content, acid insoluble ash content, specific gravity, residual ethanol solvent, total plate number contamination yeast -mold number, Pb and Cd metal contamination Results: Based on the non-specific standardization parameter test results, the ethanol extract of Phaleria macrocarpa (Scheff.) Boerl leaves met the Indonesian herbal pharmacopeia standards; however, the Cd metal contamination test exceeded the established standards. Based on one-way ANOVA analysis, there were four standardization parameters that were differed significantly (sig <0.05), namely drying shrinkage, moisture content, total ash content, and determination of heavy metal content.